ANALISIS KINERJA KEUANGAN PADA KANTOR DESA KARYA MAJU KABUPATEN TANJUNG JABUNG BARAT - Sutono, Desi Liana; Liana, Desi; Agustin Nengsih, Titin; Syah Noor, Firman (Manajemen Keuangan Syariah, 2025)
This study aims to analyze the financial performance of the Village Government of Advanced Work Forward Regency Tanjung Jabung Regency based on the ratio of decentralization, the ratio of local financial independence, the ratio of regional financial effectiveness, shopping efficiency and the growth ratio of regions. This research is a quantitative descriptive study. Using secondary data in the form of reports of the realization of the Village Revenue and Shopping Budget (APBDes) Karya Forward Regency, Tanjung Jabung West Regency, for the 2021-2024 period. The results of this study indicate that the financial performance of the Advanced Works Village government based on the ratio of decentralization degrees categorized as less, Regional financial independence ratio is categorized as low as criteria and destructive relationship patterns, the ratio of regional financial dependency on efefktif, the ratio of the effectiveness of Regional Revenue in categorized as efefktif, shopping efficiency is not efficient and growth ratios.